The influence of refrigerant (R32) flow maldistribution on the thermal performance of a microchannel heat exchanger without considering superheat and sub-cool / Chng Ming Hui, Chin Wai Meng and Tang Sai Hong - Chng, Ming Hui; Chin, Wai Meng; Tang, Sai Hong (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The research work reported in this paper investigates the numerical study on the influence of statistical moments of probability density function of R32 tube-side flow maldistribution on the thermal performance of microchannel heat exchanger. A model without considering superheat and sub-cool was developed to analyze the effect of mean, standard deviation and skew of the refrigerant maldistribution profile on the heating capacity degradation of the heat exchanger. Next, the performance degradation of microchannel heat exchanger due to refrigerant (R32) maldistribution was quantified and analyzed. After that, the model was validated by doing experiment. Finally, a performance deterioration correlation related to refrigerant maldistribution without considering superheat and sub-cool was developed to offer a faster and simpler method to analyze the maldistribution problem. It is found that mean and standard deviation have the highest impact on the performance deterioration. Maldistribution with high standard deviation and high negative skew gives a large magnitude of performance deterioration. For standard deviation more than 0.3, the deterioration can up to 1%. Besides that, the deterioration reaches 1% for skew below -0.5. Furthermore, the deterioration is as high as 4% when the mean is less than 0.9. Hence, the first three moments such as mean, standard deviation and skew should be optimized in the effort of improve the thermal performance of the heat exchanger. The proposed correlation in this work offers a faster and simpler method for a quick estimate of the degradation factor.